The endocrinology of human life history transitions - Ellison, Peter (Henry Stewart Talks, 2007)
The energy allocation model of life history evolution, Quantitative variation in energy allocation to reproduction, Endocrine control of qualitative, state transitions in human life history, Three example transitions: postpartum resumption of ovarian function, puberty, birth
Reviewed at 2020/08/16